Underwater Endoscopic Mucosal Resection of Small Rectal Neuroendocrine Tumors - Okada, Masahiro; Shinozaki, Satoshi; Ikeda, Eriko; Hayashi, Yoshikazu; Takezawa, Takahito; Fukuda, Hisashi; Morikawa, Takaaki; Kitamura, Masafumi; Arita, Munefumi; Nomura, Tatsuma; Sakamoto, Hirotsugu; Sunada, Keijiro; et al. (Frontiers in Medicine, 2022)
Background and study aims: The resection strategy for rectal neuroendocrine tumors (NET) <10mm is not uniform. We compared the utility of underwater endoscopic mucosal resection (UEMR) to endoscopic submucosal resection with a ligation device (ESMR-L) to resect rectal NETs. Patients and methods: Patients with rectal NET <10mm treated with UEMR or ESMR-L were included. Their medical records were retrospectively reviewed. Results: Thirty-two patients were divided into a UEMR group (n=7) and an ESMR-L group (n=25). Histopathological diagnosis of NET by biopsy was known before resection in 43% (3/7) in the UEMR group and 68% (17/25) in the ESMR-L group, (p=0.379). UEMR was performed on an outpatient basis for all patients, and 92% of ESMR-L (23/25) were performed as inpatient procedures (p<0.001). The procedure time was significantly shorter in the UEMR group than in the ESMR-L group (median [IQR], min, 6 [5-8] vs. 12 [9-14], p=0.002). En bloc resection and R0 resection rates were 100% in both groups. Pathological evaluations were predominantly NET G1 in both groups (UEMR: 7/7, 100% and ESMR-L: 23/25, 92%). Two patients in the ESMR-L group developed delayed bleeding, controlled by endoscopic hemostasis. Device costs were significantly higher in the ESMR-L group than the UEMR group by approximately US180 (median [IQR], 90.45 [83.64-108.41] vs. 274.73 [265.86-292.45], P<0.001). Conclusions: UEMR results in similar resection quality with shorter procedure time and lower costs compared to ESMR-L. We recommend UEMR for the resection of rectal NET <10 mm.